A bacterial artificial chromosome (BAC) genomic approach reveals partial clustering of the furanocoumarin pathway genes in parsnip. (10th February 2017) - Roselli, Sandro; Olry, Alexandre; Vautrin, Sonia; Coriton, Olivier; Ritchie, Dave; Galati, Gianni; Navrot, Nicolas; Krieger, Célia; Vialart, Guilhem; Bergès, Hélène; Bourgaud, Frédéric; Hehn, Alain
Summary: Furanocoumarins are specialized metabolites that are involved in the defense of plants against phytophagous insects. The molecular and functional characterization of the genes involved in their biosynthetic pathway is only partially complete. Many recent reports have described gene clusters responsible for the biosynthesis of specialized metabolites in plants. To investigate possible co‐localization of the genes involved in the furanocoumarin pathway, we sequenced parsnip BAC clones spanning two different gene loci. We found that two genes previously identified in this pathway, CYP71AJ3 and CYP71AJ4, were located on the same BAC, whereas a third gene, PsPT1, belonged to a different BAC clone. Chromosome mapping using fluorescence in situ hybridization (FISH) indicated that PsPT1 and the CYP71AJ3 ‐ CYP71AJ4 clusters are located on two different chromosomes. Sequencing the BAC clone harboring PsPT1 led to the identification of a gene encoding an Fe(II) α‐ketoglutarate‐dependent dioxygenase (PsDIOX) situated in the neighborhood of PsPT1 and confirmed the occurrence of a second gene cluster involved in the furanocoumarin pathway. This enzyme metabolizes p ‐coumaroyl CoA, leading exclusively to the synthesis of umbelliferone, an important intermediate compound in furanocoumarin synthesis. This work provides an insight into the genomic organization of genes from the furanocoumarin biosynthesis pathway organized in more than one gene cluster. It also confirms that the screening of a genomic library and the sequencing of BAC clones represent a valuable tool to identify genes involved in biosynthetic pathways dedicated to specialized metabolite synthesis. Significance Statement: Furanocoumarins are metabolites involved in defense against plant‐eating insects, but information about furanocoumarin biosynthesis is incomplete. Gene clusters are often responsible for synthesis of specialized metabolites, but here we show that genes committed to furanocoumarin synthesis are grouped at least on two distinct chromosomes.